Imajinasi dalam Pendidikan: Studi Kritis dalam Perspektif Pedagogik Futuristik - Waryanti Waryanti; Yusuf Tri Herlambang; Tatang Muhtar (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Imagination in education is considered to be just imagination, illusion and fantasy due to a lack of knowledge of the nature of imagination itself. This research will comprehensively discuss the fundamentals of imagination in education. The method used uses literature studies that elaborate and examine and critically sort literature sources that are relevant to the topic being researched to produce quality research. The research results show that imagination plays a very fundamental role in education, this is proven by imagination as a source of knowledge where imagination is not limited by binding principles of thought. Imagination is the result of human sensory experience which is depicted by producing ideas, thoughts or works that are original and authentic. Futuristic pedagogy is a bridge in connecting imagination with education that prioritizes the principle of humans as multidimensional creatures who have the ability to think about the future, overcome problems and answer future challenges, to provide solutions to issues in society.